Changes in free polyamines and expression of polyamine metabolic genes under drought and high-temperature in Citrus sinensis - X. Z. Fu; Y. Huang; F. Xing; C. P. Chun; L. L. Ling; L. Cao; L. Z. Peng (Biologia Plantarum, 2016)
Polyamines play important roles in plant responses to various environmental stresses. In this study, changes in free polyamine content and transcription of genes participating in polyamine metabolism were investigated in sweet orange (Citrus sinensis Osbeck cv. Jincheng) seedlings under drought (DR), high-temperature (HT), and combined DR and HT (DRHT) stresses. Content of putrescine (Put) and spermidine (Spd) was the highest and that of spermine (Spm) was the lowest under the DR stress, whereas Put and Spd content was the lowest, and Spm content was the highest under the HT stress. Content of the three polyamines under the DRHT stress ranged between the values detected under the DR and HT at most time points. The fluctuation of Put content during the three stresses was irregular; significant amounts of Spd under the DRHT and Spm under all the three stresses were accumulated. Expression of genes encoding arginine decarboxylase, Spd synthase, and Spm synthase was significantly induced under the DR but not under the HT. The relief from all the stresses did not cause an expected decrease or increase in polyamine content and expression of related genes.